Characteristics And Characterization Methodologies Of MSW At Source - A Review - Goh, C.T (University Malaysia Sarawak, (UNIMAS), 2009)
This paper presents a review on the characteristics and characterization methodologies of Municipal solid waste at sources. The method used to determine the characteristics of MSW is sampling. Materials are collected at different sources and are separated. The material is then characterized by its physical and chemical characteristics.